Atrial septal defect occluder combined with stent graft for the management of post-dissection aortic aneurysm previously treated with unsuccessful coils: a case report - Qiqi Wang; Haijun Wei; Chunshui He; Yang Liu (CVIR Endovascular, 2023)
Abstract Background Although the candy-plug technique has been reported to be useful for the treatment of post-dissection aortic aneurysm, the stent graft needs be to customized to accommodate the size of vascular occluders. Case presentation We present a case of a persistent false lumen successfully treated with endovascular stent-graft and atrial septal defect occluder in a patient with Stanford Type B dissection. A covered stent graft was implanted into the false cavity through a distal rupture, and an atrial septal defect occluder was inserted into the covered stent to seal of the false cavity. Decreased aneurysmal diameter and false lumen thrombosis were noted by CT scan at 6-month follow-up. Conclusions Our case showed that combined use of a stent graft and atrial septal defect occluder is safe, technically feasible and effective in sealing of the false lumen in post-dissection aortic aneurysm patients with previously failed false lumen thrombosis.